Optimal Fertilizer Nitrogen Rates and Yield‐Scaled Global Warming Potential in Drill Seeded Rice. Issue 6 (1st November 2013) - Adviento‐Borbe, Maria Arlene; Pittelkow, Cameron M.; Anders, Merle; van Kessel, Chris; Hill, James E.; McClung, Anna M.; Six, Johan; Linquist, Bruce A.
Abstract : Drill seeded rice ( Oryza sativa L.) is the dominant rice cultivation practice in the United States. Although drill seeded systems can lead to significant CH4 and N2 O emissions due to anaerobic and aerobic soil conditions, the relationship between high‐yielding management practices, particularly fertilizer N management, and total global warming potential (GWP) remains unclear. We conducted three field experiments in California and Arkansas to test the hypothesis that by optimizing grain yield through N management, the lowest yield‐scaled global warming potential (GWPY = GWP Mg −1 grain) is achieved. Each growing season, urea was applied at rates ranging from 0 to 224 kg N ha −1 before the permanent flood. Emissions of CH4 and N2 O were measured daily to weekly during growing seasons and fallow periods. Annual CH4 emissions ranged from 9.3 to 193 kg CH4 –C ha −1 yr −1 across sites, and annual N2 O emissions averaged 1.3 kg N2 O–N ha −1 yr −1 . Relative to N2 O emissions, CH4 dominated growing season (82%) and annual (68%) GWP. The impacts of fertilizer N rates on GHG fluxes were confined to the growing season, with increasing N rate having little effect on CH4 emissions but contributing to greater N2 O emissions during nonflooded periods. The fallow period contributed between 7 and 39% of annual GWP across sites years. This finding illustrates the need to include fallow period measurements in annual emissions estimates. Growing season GWPY ranged from 130 to 686 kg CO2 eq Mg −1 season −1 across sites and years. Fertilizer N rate had no significant effect on GWPY ; therefore, achieving the highest productivity is not at the cost of higher GWPY .